Role of miRNAs in tumor and endothelial cell interactions during tumor progression. (February 2020) - Orso, Francesca; Quirico, Lorena; Dettori, Daniela; Coppo, Roberto; Virga, Federico; Ferreira, Livia C; Paoletti, Camilla; Baruffaldi, Désirée; Penna, Elisa; Taverna, Daniela
Abstract: Cancer is a multistep disease based on crucial interactions between tumor cells and the microenvironment (extracellular matrix and stroma/immune cells). In fact, during dissemination, tumor cells have to escape from the primary tumor mass, cross the basal membrane, interact with endothelial cells to enter blood vessels (intravasation), survive in the bloodstream, get in contact with endothelial cells again to exit the bloodstream (extravasation) and seed in distant organs. Interactions between tumor and stroma cells are strongly coordinated by microRNAs (miRNAs), small non-coding RNAs able to silence protein coding genes by binding to specific recognition sites, mostly located at the 3' UTR of mature mRNAs. Relevantly, miRNA expression is often altered (overexpression or downregulation) in tumor cells and influenced by stroma cells. At the same time, miRNAs are abundant and essential in stroma cells during tumor cell dissemination and their expression is influenced by tumor cells. In fact, for instance, conditional ablation of Dicer in the endothelium of tumor bearing-mice leads to reduced tumor growth and microvessel density. In this review, we specifically focus on the role of miRNAs in endothelial cells regarding their positive or negative intervention on tumor angiogenesis or lymphoangiogenesis or when tumor cells detach from the tumor mass and intravasate or extravasate in/out of the blood vessels. Examples of pro-angiogenic miRNAs are miR-9 or miR-494, often overexpressed in tumors, which accumulate in tumor cell microvescicles and, therefore, get transferred to endothelial cells where they induce migration and angiogenesis. Differently, miR-200 and miR-128 are often downregulated in tumors and inhibit angiogenesis and lymphoangiogenesis. Instead, miR-126 controls intravasation while miR-146a, miR-214, miR-148b govern extravasation, in a positive or negative manner. Finally, at the end, we summarize opportunities for therapeutic interventions based on miRNAs acting on endothelial cells.